KORELASI ANTAR-KARAKTER DAN SIDIK LINTAS ANTARA KOMPONEN HASIL DENGAN HASIL BIJI KACANG HIJAU (Vigna radiata (L) Wilczek) - Lukman Hakim; Suyamto Suyamto (Research Center for Biology-Indonesian Institute of Sciences, 2012)
A total of 10 mungbean (Vigna radiata (L.) Wilczek) genotipes including check variety (Vima) were evaluated on rainfed after rice at Ngale Experimental Farm, Ngawi, East Java during early dry season of 2010. The experiment was conducted in randomized complete block design with three replications. Plot size was 4 m x 5 m, plant spacing was 40 cm x 20 cm, each hill contained two plants. A correlated and path coefficient analyses were used in order to determine the association among characters and quantify the direct and indirect effects of agronomy traits on seed yield. The study has identified 2 promising lines, i.e. MMC342d-3-4 and MMC342d-kp-3-3 produced the highest yield of 2.2 t and 2.0 t/ha respectively and had good adaptation on rainfed. Two varieties (Kutilang and Kenari) having large seed size (>7.5g/100 seed). Therefore, these varieties can be used as source of parents on breeding program. Among the agronomic characters, number of pods per plant, number of seeds per pod and seed size were positively and significantly correlated with grain yield. The direct effect of number of pods per plant, number of seed per pod and seed size to grain yield as indicated by path coefficient were the highest, while other causal effects to grain yield were small or negative. Based on both analyses, mungbean genotipes with high grain yield should have high number of pods per plant, number of seeds per pod and large seed size. Therefore, number of pods per plant, number of seeds per pod and seed size can be suggested for selection criteria in selecting high yield mungbean genotipes on rainfed.